2020
DOI: 10.1021/acs.jpcc.0c05623
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport in Polyaniline–Barium Ferrite Nanocomposites with Negative Giant Magnetoresistance

Abstract: The barium ferrite/polyaniline (BaFe12O19/PANI) nanocomposites with room temperature negative giant magnetoresistance (GMR) are fabricated by the surface-initiated polymerization (SIP) method. The maximum negative GMR value is −7.1% in BaFe12O19/PANI nanocomposites with a BaFe12O19 loading of 20 wt % at a magnetic field of 9 T. The electrical transport mechanism of these samples is investigated by thermally activated transport (TAT) model at the high temperature range (180–290 K) and Mott variable range hoppin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Polymer-based nanocomposites are created by combining several phases such as FE, piezoelectric, and ferromagnetic (FM) phases. 96 The type, size, shape, and loading of the nanocomposite in the polymer chain of the matrix might be varied to modify its GMR characteristics. 97 Polymer nanocomposites with customized negative permittivity might be created by adjusting their component, microstructure, and arrangement.…”
Section: Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer-based nanocomposites are created by combining several phases such as FE, piezoelectric, and ferromagnetic (FM) phases. 96 The type, size, shape, and loading of the nanocomposite in the polymer chain of the matrix might be varied to modify its GMR characteristics. 97 Polymer nanocomposites with customized negative permittivity might be created by adjusting their component, microstructure, and arrangement.…”
Section: Nanocompositesmentioning
confidence: 99%
“…Numerous factors, including surface area, permeability, aggregate morphology, fabrication circumstances, particle dispersion across the matrix, and filler loading quantity, have been linked to the shielding capacities of polymeric nanocomposites. Polymer-based nanocomposites are created by combining several phases such as FE, piezoelectric, and ferromagnetic (FM) phases . The type, size, shape, and loading of the nanocomposite in the polymer chain of the matrix might be varied to modify its GMR characteristics .…”
Section: Nanocompositesmentioning
confidence: 99%
“…The magnetoresistance (MR) phenomenon refers to the resistance variations of a material under the external applied magnetic field, 85,86 which has wide applications in the magnetic recording devices, hard disc drives and automobile speed displacement sensors. 87 The value of MR could be measured on a Physical Property Measurement System (PPMS) and calculated by eqn (9): 88 where R (H) and R (0) represent the resistance of a material under and without a magnetic field, respectively. Apart from the traditional inorganic and organic semiconductor materials, it's reported that the carbon-based materials (such as graphene and carbon nanotubes) could also serve as a kind of promising magnetoresistive material.…”
Section: Electronic Applications Of Phthalonitrile Resinsmentioning
confidence: 99%